The integration of mathematic knowledge in accounting and finances career - Tardío Rueda , Osvaldo Andrés; Carreras Sotero , Oscar Lorenzo; Pujol Bandomo, Ismeris Dayami (Revista Minerva, 2021)
The theacheIs main task is to direct the teaching process; this process can not be done correctly without a proper domain of the content, a crrect methodologic preparation and a correct use of new tecnologies. These requisements support the correct realization of this work, that has as main goal: to design a group of educational tasks to integrale the mathematic concepts from the conceptual relations in the different disciplines inside accounting and Finances Career during the meeting lessons. With the realization of these tasks me could shon that they bécame effective during the control and the evaluation of the independent work during the meeting lessons.
Keywords: Mathematic discipline; integration of mathematic concepts; educational tasks; conceptual relations; to design; counting and Finances Career